P-Phenylenediamine induces epithelial-mesenchymal transition in SV-40 immortalized human urothelial cells via the ERK5/AP-1 signaling. (1st December 2022) - Liu, Zhiqi; Zhao, Li; Sun, Wei; Zhang, Zhiqiang; Wang, Daming; Ding, Demao; Xie, Dongdong; Bi, Liangkuan; Yu, Dexin
Abstract: Purpose: To investigate whether p-Phenylenediamine (PPD) could triggered EMT inSV-40 immortalized human urothelial cells (SV-HUC-1), and the regulation role of ERK5/AP-1 during this process. Materials and methods: SV-HUC-1 cells were treated with different concentrations of PPD. MTT assay was employed to detect cell viability. Wound healing and transwell assay were performed to detect migrative and invasive capacity. Western blot and qRT-PCR were utilized for detecting molecular changes. ERK5 specific inhibitor was used to suppress ERK5 signaling. Results: Migration and invasion capacity of SV-HUC-1cells were enhanced after PPD exposure. Expression of epithelial markers E-cadherin and ZO-1 was decreased and expression of mesenchymal markers N-cadherin and vimentin was increased after being cultured with low concentrations of PPD, indicating that PPD induced EMT in PPD-cultured SV-HUC-1 cells. Meanwhile, PPD triggered activation of ERK5signaling and downstream AP-1 was activated, but no obvious influence of PPD on other sub-families of MAPK was detected. After inhibition of ERK5/AP-1, PPD-induced enhancement of migrative and invasive abilities were attenuated and expression of EMT markers was also reversed. Conclusion: PPD may be a carcinogen, which could induce EMT in SV-40 immortalized human urothelial cells (SV-HUC-1) via activating ERK5/AP-1 signaling. Highlights: PPD induces EMT in SV-40 immortalized human urothelial cells. PPD activates ERK5 rather ran other member of MAPK families. ERK5 positively regulates PPD related EMT in SV cells.